Integrating Small-Scale Tree Farmers Into Wood Markets: A Case of Tree Farmers in Central Uganda - Justine Namaalwa; Antonny Tugaineyo; Scovia Akello; Patrick Byakagaba (wiley, 2025)
Small-scale tree farmers are increasingly recognized as important producers of wood resources, yet their integration into woodmarkets remains limited in many developing countries. Integration is conceptualized as farmers’ ability to access target markets,participate in price-setting, and compete favorably for fair prices. In sub-Saharan Africa, tree growing has often been promoted forconservation or subsistence, with little emphasis on commercialization. This study was motivated by the underrepresentation ofsmall-scale farmers in wood markets despite their potential to supply signifcant wood resources and by the lack of empiricalevidence on their degree of integration into markets. The study contributes to a deeper understanding of how small-scale treefarmers are integrated into wood markets by addressing two questions. (i) Which sociodemographic and tree farm attributesinfuence access to target and fnal selling points? (ii) What factors infuence participation in price-setting? The research wasconducted in Mubende District, Central Uganda, using a mixed-methods approach. Data were collected through participant andkey informant interviews and focus group discussions. Quantitative data were analyzed using descriptive statistics, chi-square tests,and binary logistic regression, while qualitative data were processed using thematic content analysis. Findings showed that mostfarmers failed to sell from their target markets due to high transport costs, limited market information, and reliance onintermediaries. Participation in price-setting was also limited, with many farmers accepting prices ofered by buyers, especially incases of distress sales linked to urgent household needs. The study recommends that governments and development partnersstrengthen business support services, including technical training, value addition, and improved market information systems, toenable small-scales’ transition from subsistence-oriented production to efective participation in wood markets
Keywords: integration; small-scale tree farmers; transaction costs; tree farm; Uganda; wood markets; wood products; woodlot